Studium rozkladu ozónu na pevných površích - Krejsková, Eliška (Vysoké učení technické v Brně. Fakulta chemická)
Tato bakalářská práce je zaměřena na prozkoumání rozkladu ozónu, ke kterému dochází při styku s pevnými povrchy. Cílem je zjistit, který materiál rozkládá ozón nejméně, a tím pádem je nejvhodnější k výrobě potrubí pro dopravu ozónu z místa výroby do místa použití. V teoretické části jsou popsány důležité vlastnosti ozónu, způsoby jeho výroby, stanovení koncentrace a vztah ozónu k nejrůznějším pevným povrchům. V experimentální části bylo zkoumáno, v jaké míře dochází k rozkladu ozónu vlivem pěti běžně dostupných kovových materiálů (nerez, mosaz, měď, hliník a železo). Měření bylo prováděno ve skleněné trubici (Liebigův chladič), do které se vkládaly duté trubky z daných materiálů. Skrz tuto trubici procházel ozón, jehož koncentrace se na výstupu stanovovala dvěma metodami: jodometrickou titrací a spektrofotometricky. Bylo změřeno a porovnáno několik sérií při různých reakčních časech, různých experimentálních podmínkách (průtok vzduchu, výkon ozonizátoru) a při použití technického a syntetického vzduchu, jelikož vlhkost technického vzduchu má podstatný vliv na rozklad ozónu. Ze získaných výsledků bylo vyhodnoceno, že nejvhodnější materiály pro zmíněné použití jsou nerez a hliník.

This bachelor’s thesis is focused on the study of ozone decomposition which occurs during its contact with solid surfaces. The aim is to find out which material causes the lowest ozone decomposition and that is why it is the most suitable material for pipelines used for ozone transportation from a place of production to a place of application. In the theoretical part important properties of ozone, possibilities of its production, methods of ozone determination and relation of ozone to different solid surfaces were described. In the experimental part there was investigated how much ozone is decomposed by five commonly available metal materials (stainless steel, yellow brass, copper, aluminium and iron). Measurements were realized in the glass tube (Liebig condenser). Hollow pipes made of particular material were inserted into this tube. Ozone passed through this glass tube and ozone concentration was determined on its output by two methods: the iodometric titration and spectrophotometry. Several series were measured and compared by different set-up conditions like reaction time, experimental parameters (flow rate of air, input power of the ozone generator) and two types of gas – technical and synthetic air (because moisture contained in technical air can cause ozone decomposition) were used. The most suitable materials – stainless steel and aluminium were determined according to gained results.
Study of ozone decomposition on solid surfaces
Keywords: ozón; rozklad ozónu; stanovení koncentrace ozónu; jodometrická titrace; spektrofotometrie; ozone; ozone decomposition; determination of ozone concentration; iodometric titration; spectrophotometry